Analisis Keefektifan Instagram (@jinawigreens) Sebagai Media Komunikasi Pemasaran Digital Jinawi Farm Hidroponik Karanganyar - Tiara Octari Pravina; Emi Widiyanti; Putri Permatasari (Jurnal Sosial Ekonomi Pertanian, 2023)
Jinawi Farm Hidroponik is one of the businesses that develops hydroponic agricultural products into healthy food preparations in the form of vegetable salads. Of course, a marketing communication activity is needed in developing its business, one of which is through Instagram social media (@jinawigreens). The effectiveness of the Instagram account @jinawigreens as a digital marketing communication medium, can be influenced by the characteristics of the messages conveyed in it. Therefore, it is necessary to measure the effectiveness of Instagram, as well as the effect of message characteristics on its effectiveness. The EPIC Model is used as a measuring tool for effectiveness in this study. The model measures effectiveness by using a communication approach through four critical dimensions, namely empathy, persuasion, impact, and communication. This study aims to 1) analyze the characteristics of social media messages on Instagram @jinawigreens. 2) Analyzing the effectiveness of Instagram @jinawigreens social media based on the EPIC Model. 3) Analyzing the influence of the characteristics of social media messages Instagram @jinawigreens on the effectiveness of Instagram as a digital marketing communication medium for Jinawi Farm Hydroponics based on the EPIC Model.